2014
DOI: 10.1007/s10665-014-9754-x
|View full text |Cite
|
Sign up to set email alerts
|

Analytical solution and mechanisms of fluid production from hydraulically fractured wells with finite fracture conductivity

Abstract: A comprehensive study of the physical mechanisms of fluid production from a well intersected by a narrow elliptically shaped vertical fracture with finite fracture conductivity is carried out using a newly obtained analytical solution. The flow pattern, flux density distribution along the fracture surface, and fluid production rate are analyzed systematically with respect to finite fracture conductivity. The simplicity of the new analytical solution reveals many physical insights not attainable from existing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Recently, we have performed an analysis of the Darcy flow pattern in the reservoir and the flux density distribution along the fracture-reservoir surface, using a newly obtained analytical solution for finite fracture conductivities [2,3]. It is found that when the well pressure is lowered, the induced-flow in the reservoir develops a converging pattern that focuses the fluid to the fracture tip, creating a nearly singular flux density around the fracture tip.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have performed an analysis of the Darcy flow pattern in the reservoir and the flux density distribution along the fracture-reservoir surface, using a newly obtained analytical solution for finite fracture conductivities [2,3]. It is found that when the well pressure is lowered, the induced-flow in the reservoir develops a converging pattern that focuses the fluid to the fracture tip, creating a nearly singular flux density around the fracture tip.…”
Section: Introductionmentioning
confidence: 99%
“…According to some simple exact solutions, 24,25 in fractured porous media, pore fluid flow towards a fracture develops a pressure-gradient singularity at the fracture tip. Because the fracture possesses sharp ends, the potential flows around a thin plate develop a velocity singularity at the ends of the plate.…”
Section: Enrichment Schemementioning
confidence: 99%
“…25 The used formulations in the exact solution can be found in Appendix. 25 The used formulations in the exact solution can be found in Appendix.…”
Section: Comparison Between Numerical and Analytical Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mathematically, the solution to the boundary-value problem for a domain slightly distorted from a circular area can be rigorously pursued by the method of domain perturbation in which the solution is expanded in a Tayler-series expansion in terms of the small geometrical distortion (Joseph 1973). In this spirit, the solutions obtained by Prats and coworkers and Chen and coworkers with shape approximation are actually the leading-order solutions in these Taylor-series expansions.…”
Section: Modeling Production From a Fractured Well In A Circular Draimentioning
confidence: 99%